Meningkatkan Kemampuan Kognitif dengan Metode Membaca Buku Dongeng Pada Anak di Panti Asuhan Al Kahfi Medan - Fenty Zahara Nasution; Ayu Gustania Dalimunthe (BADAN PENERBIT STIEPARI PRESS, 2021)
This study aims to provide fairy tales and see their cognitive abilities, by providing a method of reading fairy tales to children at the Al Kahfi Orphanage Medan is a very interesting activity for children. ages 7 to 12 years, Piaget divided cognitive development into four phases, namely the sensorimotor phase, the pre-operational phase, the concrete operations phase, and the formal operational phase Concrete Operations phase (ages 7-12 years). logical thinking has developed, provided that the object that is the source of logical thinking is present concretely. Thinking ability is characterized by mental activities such as remembering, understanding and being able to solve problems. Children are better able to think, learn, remember and communicate because their cognitive processes are no longer egocentrism and are more logical. Children are invited to play fairy tales to train their cognitive abilities, because fairy tales are stories that are told for entertainment which usually do not actually happen in life. Fairy tales are a form of literary work whose stories are fictitious or not really happening and are entertaining and in fairy tales there are moral teachings. By listening to fairy tales, children like entertaining games while honing cognitive skills when the storyteller asks again about the content of the story. Types Animal tales (animal tales), is a fairy tale with the characters in the story are wild animals and pets. These animals are likened to be able to talk and behave like humans. A special form of animal fables is fables. Fabels itself is an animal fairy tale that contains a moral message in it, namely good behavior and bad behavior, Sikancil stories from storytellers that have been conceptualized with appropriate themes, plots and backgrounds, children have actually carried out cognitive processes.